Documents on the Greek Community of Turkey - –, – (Études helléniques / Hellenic Studies, 2001)
In this issue we publish two documents on the destruction of the Greek Community of Turkey during the violent events of September 6, 1955. The first document is from the archives of the US State Department and the second from the archives of the French Ministry of Foreign Affairs. The French document, published herein for the first time, stems from the research of our collaborator Jean Catsiapis, who has been consulting these archives for many years now. The American text was published by professor Speros Vryonis in 1996. Professor Vryonis noted at his presentation: "The pogrom of 1955 was a Turkish "success" as it finally descroyed the ancient Hellenism of Constantinople, both in its physical and psychological dimensions".